1954
DOI: 10.1113/jphysiol.1954.sp005221
|View full text |Cite
|
Sign up to set email alerts
|

The sensation of passive movement at the metatarso‐phalangeal joint of the great toe in man

Abstract: This work was begun as an investigation into the characteristics of passive movement sense at the metatarso-phalangeal joint. Since the original work of Goldscheider (1889), other investigators (Winter, 1912; Laidlaw & Hamilton, 1937 a, b;Cleghorn & Darcus, 1952) have investigated joint sensation in normal subjects by measuring the response to a continuous movement. Their work established the existence of threshold speeds of movement, varyingwith different joints in different subjects, below which sensation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
2

Year Published

1957
1957
1984
1984

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 7 publications
3
32
2
Order By: Relevance
“…Experiments such as those of Gelfan and Carter (1967), who artificially manipulated muscle length and tension by pulling on surgically exposed tendons, are considered to be employing passive movements, since the movements are not actively induced by the subject. However, different results are obtained when active movement is employed (Browne et al, 1954;Lloyd & Caldwell, 1965;Merton, 1964), the anesthetized judgments were made, F(4,44) = 3.66, p < .05. When the sum of squares for trials was partitioned (Rodger, 1965), the linear component of the trend was found to be significant, F (1,44) = 13.84, p < .001, whereas the residual component was not, F(3,44) = 0.26, P > .05.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments such as those of Gelfan and Carter (1967), who artificially manipulated muscle length and tension by pulling on surgically exposed tendons, are considered to be employing passive movements, since the movements are not actively induced by the subject. However, different results are obtained when active movement is employed (Browne et al, 1954;Lloyd & Caldwell, 1965;Merton, 1964), the anesthetized judgments were made, F(4,44) = 3.66, p < .05. When the sum of squares for trials was partitioned (Rodger, 1965), the linear component of the trend was found to be significant, F (1,44) = 13.84, p < .001, whereas the residual component was not, F(3,44) = 0.26, P > .05.…”
Section: Resultsmentioning
confidence: 99%
“…Studies using passive movement of the extremities following anesthesia (Browne et al, 1954;Gelfan & Carter, 1967;Merton, 1964;Provins, 1958) seem to suggest that muscle spindle receptors are not responsible for any sense of passive movement, whether the paradigm calls for perception of the position of the limb in space or threshold of movement. Experiments such as those of Gelfan and Carter (1967), who artificially manipulated muscle length and tension by pulling on surgically exposed tendons, are considered to be employing passive movements, since the movements are not actively induced by the subject.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Wall and Noordenbos (1977) studied three patients with surgically confirmed lesions of the dorsal columns and after testing sensation in a variety of ways concluded that there was no loss of the classical primary modalities of sensation but loss of an ability to carry out tasks where one must simultaneously analyze spatial and temporal characteristics of the stimulus. A review of their methods of testing for JPS suggests that it was probably markedly or completely lost especially since one can accurately detect 0.5 degrees of movement at the hip even after total hip replacement surgery (Karenjia and Ferguson, 1983) and 4.4 degrees of movement at the great toe (Browne et al, 1954). In the case of vibration sense, Calne and Pallis (1966) propose that it represents a temporal modulation of tactile sense, that it is not a specific "modality," that the relevant impulses ascend in both the dorsal and lateral columns, and that the physiological implications of "posterior column signs'' are redundant as they are based upon inadequate clinicopathological correlations.…”
Section: Discussionmentioning
confidence: 99%
“…Systems as diverse ashydraulic (Goldscheider, 1889;Horch, Clark, & Burgess, 1975), electromechanical (Browne, Lee, & Ring, 1954;Gandevia & McCloskey, 1976;Kokmen, Bossemeyer, & Williams, 1977), and even manual (Laidlaw & Hamilton, 1937) have all been used. Similarly, there have been wide differences in the techniques used to measure the angular displacement threshold, including reading the values from a scale (Browne et al, 1954;Goldscheider, 1889;Laidlaw & Hamilton, 1937), from an ink-writer deflection (proportional to the angular displacement) (Gandevia & McCloskey, 1976;Horch et al, 1975), and even from a minicomputer digital display (Kokmen et al, 1977). Of equal importance with the differences in measurement technique is the fact that none of the systems used so far has included a brake mechanism to terminate rotation when the response is made.…”
mentioning
confidence: 99%